Prion-like properties of assembled TDP-43. (April 2020) - Nonaka, Takashi; Hasegawa, Masato
Highlights: Abnormal TDP-43 aggregates have prion-like properties. Insoluble TDP-43 accumulated in neuronal cells is propagated to other cells and Serves as seeds for further TDP-43 aggregation in them. Suppression of propagation of pathological aggregates may be a therapeutic strategy for common neurodegenerative diseases. Abstract : A neuropathological hallmark of most neurodegenerative diseases is the appearance of characteristic inclusions composed of misfolded proteins in brains of patients. Increasing evidence shows that aggregation-prone proteins such as tau, α-synuclein and TDP-43 are accumulated in a seed-dependent and self-templating manner in vitro and in vivo, suggesting that pathological protein aggregates found in these diseases function like abnormal prion protein. Indeed, insoluble tau and α-synuclein aggregates are transferred from cell to cell both in vitro and in vivo, indicating that prion-like propagation of aberrant protein aggregates may play a key role in the pathogenesis of most neurodegenerative diseases. Here, we will review the prion-like properties of TDP-43, and discuss the molecular mechanisms underlying the propagation of these accumulated proteins. The idea that aberrant protein aggregates propagate in a prion-like manner between cells opens up the possibility of novel therapeutic strategies to block the spread of these aggregates throughout the brain.